Development of Conductive Polymer-Based Materials for Flexible Integrated Electronic Applications - Maulana, Adrian; Rifanza, M Habil; Rambe, Jefri Saidi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
As electronic devices become more common, EMI is turning into a bigger issue. Conductive polymer composites are considered promising because they are lightweight, resistant to corrosion, easy to shape, and stable. Adding conductive fillers such as graphene, MXene, carbon fibers, or certain metals can further improve their ability to block EMI and conduct heat and electricity. These materials are very thin, but they can block sounds louder than 80 dB. 3D printing and template fabrication are two new ways of making things that allow you to create strong and flexible conductive networks with little filler. However, there are still some issues that need to be addressed, such as how to distribute the filler evenly, control the microstructure, and keep the polymer-filler interface dense. Some proposed improvements are to modify the interface, mix different types of fillers, and build structures that are porous or have more than one layer. If designed and manufactured correctly, these conductive polymer composites can be used in flexible electronics, wearable devices, and next-generation thermal management systems